2001
DOI: 10.1046/j.1365-2672.2001.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory effects of whey retentate from Bifidobacteria fermented milk on the microbiota of the Simulator of the Human Intestinal Microbial Ecosystem (SHIME)

Abstract: Aims: To investigate the effects of whey retentate from Bi®dobacteria fermented milk. Methods and Results: The simulator of the human intestinal microbial ecosystem (SHIME) was used. The composition of the microbiota and its metabolic activities were analysed. Changes in the microbial composition became apparent within 15 days of the treatment in the vessels representing the ileum and the large intestine. The whey retentate favoured the growth of endogenous bi®dobacteria and induced a decrease in Bacteroides f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Accumulation was also greater in the distal colon vessel of the gut reactor, regardless of treatment conditions, resulting from prolonged fermentation similarly observed in the study of Chaikham and Rattanasena (2017). On the other hand, Tir Touil Meddah et al (2001) observed an overall decline in ammonium concentration during SHIME treatment with Bifidobacterium longum whey retentate. The findings of demonstrated an increase in tyramine and cadaverine concentrations following semi-continuous colon model supplementation of some specific oligosaccharides, Mäkeläinen, Ottman, Forssten et al (2010) showed that probiotic B. lactis Bi-07 supplementation alone, or in combination with polydextrose, significantly increased the production of cadaverine and spermine, while treatments of galacto-oligosaccharide showed complete suppression and reduction in the levels of specific BA in the colon simulations.…”
Section: Ammonia and Biogenic Aminessupporting
confidence: 59%
“…Accumulation was also greater in the distal colon vessel of the gut reactor, regardless of treatment conditions, resulting from prolonged fermentation similarly observed in the study of Chaikham and Rattanasena (2017). On the other hand, Tir Touil Meddah et al (2001) observed an overall decline in ammonium concentration during SHIME treatment with Bifidobacterium longum whey retentate. The findings of demonstrated an increase in tyramine and cadaverine concentrations following semi-continuous colon model supplementation of some specific oligosaccharides, Mäkeläinen, Ottman, Forssten et al (2010) showed that probiotic B. lactis Bi-07 supplementation alone, or in combination with polydextrose, significantly increased the production of cadaverine and spermine, while treatments of galacto-oligosaccharide showed complete suppression and reduction in the levels of specific BA in the colon simulations.…”
Section: Ammonia and Biogenic Aminessupporting
confidence: 59%
“…For this purpose, the Simulator of Human Intestinal Microbial Ecosystem (SHIME) was used. This in vitro system has already been used for several nutrition studies (De Boever et al ., 2000; Meddah et al ., 2001; Van de Wiele et al ., 2004; 2007; Decroos et al ., 2006; Ranganathan et al ., 2006) and resulted to be a useful tool for predicting in vivo events, in terms of intestinal microbial composition and activity (Molly et al ., 1993). For instance, the SHIME results of a synbiotic treatment, using hop and Eubacterium limosum , were recently validated by Possemiers and colleagues (2006; 2008) and Bolca and colleagues (2007) using human microbiota‐associated rats and human trials.…”
Section: Introductionmentioning
confidence: 99%
“…This is a more realistic replication of the conditions in the intestine [4]. Another system, the Simulator of the Human Intestinal Microbial Ecosystem (SHIME), consists of 5 to 6 serially connected pH controlled bioreactors [5-7]. The setup is quite complex and demands absolute anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%